2007
DOI: 10.4065/82.10.1185
|View full text |Cite
|
Sign up to set email alerts
|

Participation Bias and Its Impact on the Assembly of a Genetic Specimen Repository for a Myocardial Infarction Cohort

Abstract: Objective-To assess participation bias in the assembly of a specimen repository for genetic studies and to examine the association of participation with outcome within the Olmsted County myocardial infarction (MI) cohort. January 1, 1979, to May 31, 2006, 3081 persons had MI in Olmsted County, MN. Face-to-face contact was used to recruit patients who were hospitalized for an acute event. Persons who had had an MI before establishment of this repository were contacted by mail. At initial contact, we sought cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Further clouding the literature is that most genetic studies have not adequately described populations from which samples were recruited, precluding an assessment of participation bias and potentially affecting internal and external validity [5]. The only study we are aware of examining genetic participation rates in an MI registry found significant clinical differences between participants and non-participants [13], calling into question the external validity of this study. A better understanding of the variability in patients' willingness to participate in genetic studies of acute cardiovascular disease is needed to assess for selection biases and to identify opportunities to improve participation and optimize the generalizability of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Further clouding the literature is that most genetic studies have not adequately described populations from which samples were recruited, precluding an assessment of participation bias and potentially affecting internal and external validity [5]. The only study we are aware of examining genetic participation rates in an MI registry found significant clinical differences between participants and non-participants [13], calling into question the external validity of this study. A better understanding of the variability in patients' willingness to participate in genetic studies of acute cardiovascular disease is needed to assess for selection biases and to identify opportunities to improve participation and optimize the generalizability of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when we assessed the benefits of taking the lesson, a difference (0.91 in mean correct answers) was found in favour of those who opted to participate in that second part of the survey. Despite the differences being small, it may still affect our results due to a participation bias 26. Finally, no mechanism existed to prevent the physicians surveyed from using reference materials, though it was written in the instructions not to.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we investigated the association between 347 single-nucleotide polymorphisms (SNPs) within candidate genes of the proinflammatory cytokine families, including TNF (18 genes), IL-1 (10 genes), and IL-6 (12 genes), and peripheral neutrophil count in a nested case-control study from the Olmsted County, Minnesota, cohort of incident MI. 28 This study tests the hypothesis that variants within candidate genes of these proinflammatory cytokine families are associated with peripheral neutrophil count in patients with MI.…”
Section: Discussionmentioning
confidence: 99%
“…29 Details of assembly of the DNA repository that was used for the identification and recruitment of participants in this study have been previously published. 28 The current study design was a case-control study of white patients nested in the incident MI cohort. The case group consisted of 400 patients with MI and post-MI HF (HF within 90 days after MI), and the control group consisted of 694 MI patients who did not experience post-MI HF (within 90 days after MI).…”
Section: Methodsmentioning
confidence: 99%